2016
DOI: 10.1097/jom.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, Dietary, and Exercise Behavioral Clusters Among Truck Drivers With Obesity

Abstract: Objective Our objectives were to describe a sample of truck drivers, identify clusters of drivers with similar patterns in behaviors affecting energy balance (sleep, diet, and exercise), and test for cluster differences in health and psychosocial factors. Methods Participants’ (n=452, BMI M=37.2, 86.4% male) self-reported behaviors were dichotomized prior to hierarchical cluster analysis, which identified groups with similar behavior co-variation. Cluster differences were tested with generalized estimating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 33 publications
(35 reference statements)
1
46
1
15
Order By: Relevance
“…They did Effect of stress on food intake N. R. W. Geiker et al 89 obesity reviews not report, however, the proportion of very short and very long sleepers, which might be of relevance to health. Studies specifically assessing poor and short sleep and very long sleep found both associated with increased levels of mental stress and obesity (83)(84)(85)(86). Among children and adolescents, results are more consistent and show a decline in sleep duration of more than 1 h per night (87), most prevalent among children and adolescents of racial/ethnic minorities and those with low socioeconomic status (88).…”
Section: Secular Trends In Sleep Durationmentioning
confidence: 99%
“…They did Effect of stress on food intake N. R. W. Geiker et al 89 obesity reviews not report, however, the proportion of very short and very long sleepers, which might be of relevance to health. Studies specifically assessing poor and short sleep and very long sleep found both associated with increased levels of mental stress and obesity (83)(84)(85)(86). Among children and adolescents, results are more consistent and show a decline in sleep duration of more than 1 h per night (87), most prevalent among children and adolescents of racial/ethnic minorities and those with low socioeconomic status (88).…”
Section: Secular Trends In Sleep Durationmentioning
confidence: 99%
“…Diet, calorie expenditure, diabetes, stress, and quality and quantity of sleep all appear clustered around obesity. 6870 Workers with obesity are over-represented vs the general population in certain occupations. 32,70,71 For example, one study found that non-Hispanic white males who worked in health care support (36.3%), protective service (34.3%), and transportation and material moving (33.7%) had the highest prevalence of obesity while among non-Hispanic white female workers, the highest prevalence of obesity was in farming/fishing/forestry (35.9%), transportation and material moving (31.5%), and production (30.4%).…”
Section: Impact Of the Workplace On Obesitymentioning
confidence: 99%
“…Cabe citar que existem outras técnicas de comparação entre vetores com outras medidas de similaridade, como distância de cossenos (cosine similarity) e similaridade de Jaccard, entre outras 16,17 . Alguns estudos na área da saúde, como o estudo realizado por Olson et al 18 , utilizaram o algoritmo k-means para agrupamento de perfis. Nesse estudo 18 , foram agrupados perfis de caminhoneiros de acordo com atributos comuns, como duração do sono, prática de exercícios e hábitos alimentares.…”
Section: Aprendizagem Não Supervisionadaunclassified
“…Alguns estudos na área da saúde, como o estudo realizado por Olson et al 18 , utilizaram o algoritmo k-means para agrupamento de perfis. Nesse estudo 18 , foram agrupados perfis de caminhoneiros de acordo com atributos comuns, como duração do sono, prática de exercícios e hábitos alimentares. Outro estudo, realizado por Lee et al 19 , utilizou uma variação do algoritmo k-means para agrupar perfis de equipes médicas de acordo com um questionário que avaliou a incidência e grau da síndrome de burnout.…”
Section: Aprendizagem Não Supervisionadaunclassified
See 1 more Smart Citation